You have new items in your feed. Click to view.
Q: Light sensitivity in euglena is provided by the eyespot. True or False?
A: True. Light sensitivity in euglena is provided by the eyespot.
stan_r|Points 772|
Question
Updated 2/3/2014 10:15:32 AM
Edited by andrewpallarca [2/3/2014 10:15:30 AM], Confirmed by andrewpallarca [2/3/2014 10:15:32 AM]
Rating

Questions asked by the same visitor
What are the terms in the expression x3 - 5x - 18 + 8x2? Solution: User: What are the terms in the expression x3 - 5x - 18 + 8x2? Solution:
Weegy: The answer is x=(1)/(2). [ 5-(x+2)=5x Multiply -1 by each term inside the parentheses (x+2). 5-(x)-(2)=5x Multiply -1 by the x inside the parentheses. 5-x-(2)=5x Multiply -1 by the 2 inside the parentheses. 5-x-2=5x Subtract 2 from 5 to get 3. 3-x=5x Since 5x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 5x from both sides. 3-x-5x=0 According to the distributive property, for any numbers a, b, and c, a(b+c)=ab+ac and (b+c)a=ba+ca. Here, x is a factor of both -x and -5x. 3+(-1-5)x=0 Subtract 5 from -1 to get -6. 3+(-6)x=0 Remove the parentheses. 3-6x=0 Since 3 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 3 from both sides. -6x=-3 Divide each term in the equation by -6. -(6x)/(-6)=-(3)/(-6) Move the minus sign from the denominator to the front of the expression. -(-(6x)/(6))=-(3)/(-6) Cancel the common factor of 6 in -(6x)/(6). -(-( 6 x)/( 6 ))=-(3)/(-6) Remove the common factors that were cancelled out. -(-x)=-(3)/(-6) Multiply -1 by the -x inside the parentheses. -1*-x=-(3)/(-6) Multiply -1 by -x to get x. x=-(3)/(-6) Move the minus sign from the denominator to the front of the expression. x=-(-(3)/(6)) Cancel the common factor of 3 in -(3)/(6) since -(3)/(6)=((-1*3))/((2*3)). x=-(-( 3 )/(2 6 )) Remove the common factors that were cancelled out. x=-(-(1)/(2)) Multiply -1 by the -(1)/(2) inside the parentheses. x=-1*-(1)/(2) Multiply -1 by -1 to get 1. x=(1)/(2). Hope this helps. ] User: Score: Simplify 6(x + y) + (x - y). 6x 7x 7x + 6y 7x + 5y User: Simplify 6(x + y) + (x - y). Weegy: What is your question? :) User: Score: Simplify 6(x + 2) + 7. 6x + 9 6x + 15 6x + 19 Weegy: 6 x 7 = 42 ? User: Score: Simplify 6(x + 2) + 7. (More)
Question
Updated 6/30/2014 1:11:36 AM
6(x + y) + (x - y)

=6x+6y+x-y

=7x+5y
6(x+2)+7

=6x+12+7

=6x+19
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 230 [Total 248] Ratings 0 Comments 160 Invitations 7 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
L
R
Points 105 [Total 256] Ratings 1 Comments 5 Invitations 9 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Online
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
Points 20 [Total 20] Ratings 1 Comments 0 Invitations 1 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.